Types, levels and causes of post-harvest milk and dairy losses in sub-Saharan Africa and the Near East: Phase one synthesis report - Lore, Tezira A.; Omore, Amos O.; Staal, Steven J. (International Livestock Research Institute, 2004)
The following report synthesizes and highlights the types, causes and levels of postharvest milk and dairy product losses in Ethiopia, Kenya, Syria, Tanzania and Uganda, based on national study documents submitted by consultants from the respective countries. The dairy industry strengths, weaknesses, opportunities and threats in each country are also discussed. Based on these, recommendations on the next steps have been suggested.